고려대학교 박물관 소장 "경복궁배치도"의 제작시기와 사료가치(史料價値)에 대한 연구 - 이혜원; Yi, Hye-Won (건축역사연구, 2008)
Kyeongbokgung succeeded in regaining its status as a royal palace after the reconstruction that began in the second year of King Gojong(1865) only to have most of its buildings taken down in the early 20th century. Fortunately, however, there is the Pukkwoldohyong(Map of North Palace), which drew out each of the buildings of Kyeongbokgung and their arrangement in details in 1907 when the royal palace lost its original appearance. And there is another plot plan of the royal palace at the Korea University Museum, which labeled it Kyeongbokgung-Baechido(Planning Map of Kyeongbokgung Palace). The map presents almost the same plan as Pukkwoldohyong in terms of making and expressive methods, being estimated to have been made in 1888 since its building arrangement doesn't show the changes made after 1890. The map also offers more information about the uses of each building than Pukkwoldohyong and matches the excavation results of the relics. Kyeongbokgung-Jeondo(Map of Kyeongbokgung Palace), which is recorded to be made during the reconstruction of the palace in the early years of King Gojong in historical materials, describes the shapes and arrangements of the buildings in a concrete and realistic fashion. The Kyeongbokgung-Baechido seems to be one of the plans made in the process of restoring and repairing buildings that were lost or destroyed in fire. The Kyeongbokgung-Baschido has the following historic values; 1) it provides dues to estimate the early state of the palace after the reconstruction during the reign of King Gojong. In fact the Sujeongjeon and Heungbokjeon show the early state of the reconstruction; 2) it contains data with which to understand the changes to the palace after 1890, around which they added Hamhwadang and Jibokjae; and 3) it offers information about the uses of the palace's buildings from 1885 to 1880 with its descriptions of the building purposes and relationships regarding the life in the palace.